Staff Capacity Development Initiatives That Support the Well-being of Indigenous Children in Their Transitions to Boarding Schools: A Systematic Scoping Review - Heyeres, Marion; McCalman, Janya; Bainbridge, Roxanne; Redman-MacLaren, Michelle (Frontiers in Education, 2017)
Background Secondary education for Indigenous children from remote communities requires separation from their communities and families. As these students transition to boarding schools, they face several challenges which are additional to those faced by their non-Indigenous peers. In response, adequate academic and emotional wellbeing support needs to be provided by school and residential staff. This systematic review reports on international and Australian capacity development initiatives for education and boarding staff that support these students. Methods Five databases were searched using database specific search strings, considering peer-reviewed articles and grey literature, published between 2001 and 2016. The resultant publications were screened to identify a) their nature and quality, and b) their characteristics in terms of aims, strategies and outputs. Results 736 citations were identified; 51 full text publications met inclusion criteria for assessment. Seven publication were eligible for review. Staff capacity building initiatives encompassed a range of approaches, including training, feedback, reflective practice, mentoring, networking, and supervision. Only one publication focused specifically on the support of education staff, others were centred on improving educational, behavioural, and emotional outcomes for Indigenous boarding school students. All of the research was descriptive, with only two publications original research projects. Conclusion Despite a variety of approaches being described in brief, we found no high quality research that focused exclusively on staff capacity building approaches in the Indigenous boarding school context. That the few publications available to review were exclusively descriptive in nature highlights a clear need for well-executed evaluation research.